Bioactivity of Citrus hystrix D.C. Leaf Extract Against Cigarette Beetle Lasioderma serricorne (F.) - Silvi Ikawati; Moh. Syamsu Dhuha; Toto Himawan (Journal of Tropical Life Science, 2017)
The major control of pest stored Lasioderma serricorne for using synthetic pesticides, look like phosphine. Although quite effective, synthetic pesticides have a negative effect on the environment, such as pest re-sistance, deadly natural enemies, residues that are harmful to the environment and human health. The use of botanical pesticides as an alternative control be the focus this study. Botanical pesticides are selective to the target, safe for non-target insects and the environment. This research studies the repellent and fumigant activi-ty of the leaf extract of Citrus hystrix against all L. serricorne life stage. The results of GC-MS analysis of leaf crude extracts of C. hystrix with N-hexane solvent showed the highest percentage in the citronellal compound (86.43%). C. hystrix leaf extract showed stronger fumigant against pupae and eggs, compared adults, and larvae. The toxicity of the leaf extract of C. hystrix increased with increasing concentration. At a concentration of 60 ppm, fumigant activity showed the toxicity of 98.75% (pupae), 93.75% (eggs), 86.25% (adults) and 76.25% (larvae). Sequentially the LC50 value of fumigant activity from the highest to the lowest as follows; larvae 47.56 ppm, adults 43.42 ppm, eggs 31.61 and pupae 29.63 ppm. Extract of leaves of C. hystrix, have character repellent against L. serricorne. At a concentration of 60 ppm the IR value of 66% including repellent class IV, which means strong repellent level. Based on the results of the research, extracts of leaves of C. hystrix has a fumigant activity and repellent for controlling L. serricorne.